Complementary and Alternative Medicine Use in Individuals Presenting for Care at a Comprehensive Cancer Center. (March 2017) - Judson, Patricia L.; Abdallah, Reem; Xiong, Yin; Ebbert, Judith; Lancaster, Johnathan M.
Purpose: To define the use of complementary and alternative medicine (CAM) in individuals presenting for care at a comprehensive cancer center.Patients and Methods: A total of 17 639 individuals presenting to an NCI-designated Comprehensive Cancer Center (and consortium sites) completed a questionnaire regarding CAM use. Data were analyzed using the univariate χ 2 test to assess CAM use associated with a number of variables, including cancer status, age, gender, marital status, ethnicity, race, employment, and education level.Results: Eighty-seven percent of individuals who completed the CAM survey acknowledged CAM therapy use within the previous 12 months. Of the 5 broad categories of CAM, the most commonly used were biologically based approaches (14 759/17 639 [83.67%]), mind-body interventions (4624/17 485 [26.45%]), manipulative and body-based therapies (3957/17 537 [22.56%]), alternative medical systems (429/15 952 [2.69%]), and energy therapies (270/15 872 [1.7%]). CAM use was more prevalent among women, non-Hispanics, Caucasians, patients 60 to 69 years of age, and those who are married, have a higher level of education, and are employed ( P < .005).Conclusions: This is the largest report of CAM use in individuals presenting for care at a comprehensive cancer center. Our analysis revealed that a very high percentage of patients utilize CAM. Because many of these CAM interventions are not studied in oncology patients, additional research on safety, efficacy, and mechanisms of action are essential. Furthermore, it is important that oncologists understand CAM modalities and counsel their patients about their use.